## To correctly evaluate the expression -3-2^3-(-3)^3:

1. Start by solving the exponentiation. In this case, 2^3 means 2 raised to the power of 3. So, 2^3 = 2 * 2 * 2 = 8.

2. Next, evaluate the expression (-3)^3. The parentheses indicate that you need to raise -3 to the power of 3. So, (-3)^3 = -3 * -3 * -3 = -27.

3. Now substitute the results back into the original expression. -3 - 8 - (-27) becomes:

-3 - 8 + 27

4. Continue simplifying by performing the subtraction and addition:

-3 - 8 + 27 = -11 + 27 = 16

Therefore, the correct answer is 16.

Now let's evaluate the expression -2-2^2-2^3-(-2)^3:

1. Start by solving the exponentiation. 2^2 means 2 raised to the power of 2, so 2^2 = 2 * 2 = 4.

2. Next, evaluate 2^3. 2^3 means 2 raised to the power of 3, so 2^3 = 2 * 2 * 2 = 8.

3. Now, substitute these results back into the original expression: -2 - 4 - 8 - (-8).

4. The last term, (-2)^3, implies that we need to raise -2 to the power of 3. So, (-2)^3 = -2 * -2 * -2 = -8.

5. Substitute this value back into the expression: -2 - 4 - 8 - (-8) = -2 - 4 - 8 + 8.

6. Continue simplifying by performing the subtraction and addition: -2 - 4 - 8 + 8 = -6 - 8 + 8.

7. Finally, perform the remaining subtraction: -6 - 8 + 8 = -14 + 8 = -6.

Therefore, the correct answer is -6.

It seems you made a mistake when evaluating (-2)^3. Please recheck your calculations to find the correct result.